Promising practices for engaging families in literacy - Kreider, Holly; Caspe, Margaret; Hiatt-Michael, Diana B. (Family, school community partnerships, 2013)
(sponsored by the Family School Community Partnership Issues SIG)Promising Practices for Engaging Families in Literacy fulfills the need from parents and teachers to improve home/school assistance in every child's literacy development. Literacy skills are required and valued in all academic areas and at all levels of education from preschool through adulthood.This volume provides suggestions and support to improve parent/child involvement in literacy activities from preschool through teacher education programs. Research is provided to undergird the documented practices that increase student academic achievement through improved literacy skills across academic areas. Practices include connections between home and school across age groups, developmental needs groups, universities, community groups, and technologies.